Modulation of calcium current gating in frog skeletal muscle by conditioning depolarization. - Feldmeyer, D (1992)
1. Ca2+ inward currents were measured by voltage clamping cut skeletal muscle fibres of the frog (Rana esculenta) in a double-Vaseline-gap system. 2. In order to study the basis of the previously described fast gating mode induced in the Ca2+ inward current by a conditioning depolarization we quantitatively analysed the response to differing features of the conditioning prepulse. 3. The faster activation seen during the second of two depolarizations was confined to the component of the inward current which could be blocked by 5 to 10 microM nifedipine. 4. By applying depolarizing conditioning pulses of gradually increasing length the time course of the transition to the fast gating mode could be determined. 5. Both the transition to the fast gating mode (point 4) caused by a depolarization and the slow inward current activated during the same depolarization showed similar voltage-dependent kinetics. 6. The kinetic change of the test current appeared to be equal when the same fractional activation was achieved at the end of the conditioning pulse independent of its duration or amplitude. 7. Flash photolysis of nifedipine in the interval between conditioning and test pulse showed that the predepolarization causes a rate-enhancing effect even though the slow channels were blocked by nifedipine during the conditioning pulse. 8. We conclude that the transition of the calcium channel from its slow to its fast gating mode is determined by the slow voltage-dependent reaction which limits the rate of channel opening under control conditions. This reaction is apparently not prevented by the binding of nifedipine and the block of current flow through the channel.